Kerentanan Sosial Ekonomi dan Resiliensi Keluarga Petani Miskin Selama Pandemi COVID-19: Kasus Dari Madura - Hoiril Sabariman; Anik Susanti (Brawijaya Journal of Social Science, 2021)
In addition to health, the Covid-19 pandemic causing serious impact to people's socioeconomic vulnerabilities. Socio-economic vulnerabilities due to the Covid-19 pandemic forced people to adaptation, one of which was a poor peasant family in rural Madura. This article presents the results of research focusing on the socio-economic vulnerability of poor peasant family as well as various efforts in dealing with the Covid-19 pandemic. Descriptive qualitative approach and data collection method through participation observation, interviews, airy records, and documentation, this study revealed that the socioeconomic vulnerability of poor peasant family in Ponteh Village resulted from social restrictions so that the household income sector decreased. Though they have to adaptation to meet the cost of household consumption, health threats in the Covid-19 pandemic. Resilience carried out by poor peasant family in rural areas is, first, building group solidarity according to values and norms that are strong, for example, mutual help in the form of basic needs. Second, every poor peasant family makes use of very strong family ties. Parental assistance as a source of supporting living is now a basic source used to make ends meet during pandemics. Third, poor peasant family in rural areas minimize household spending and utilize social networks for business development. The contribution of this article is to provide views, efforts, accompanied by resilience in keeping the public from the threat of future pandemics.